Clinical, Functional, and Economic Ramifications of Early Nonresponse to Antipsychotics in the Naturalistic Treatment of Schizophrenia - Ascher-Svanum, Haya (Oxford University Press, 2008)
Objective: Early nonresponse to antipsychotics appears to predict subsequent nonresponse to treatment when assessed in randomized controlled trials of predominately acute inpatients treated for schizophrenia. This study assessed the predictive accuracy of early nonresponse to treatment and its clinical, functional, and economic ramifications in the naturalistic treatment of predominately chronic outpatients treated for schizophrenia. Methods: This post hoc analysis used data from a 1-year, randomized, open-label study of olanzapine, risperidone, and typical antipsychotics in the treatment of schizophrenia. If clinically warranted, patients could switch antipsychotics following 8 weeks of treatment. Patients completing 8 weeks of treatment (n = 443 of 664 enrollees) were included. Patients with early response (≥20% improvement from baseline on the Positive and Negative Syndrome Scale at 2 weeks) were compared with early nonresponders on symptom remission, functionality, perceptions of medication influence, and total health care costs at 8 weeks. Results: Early response/nonresponse at 2 weeks predicted subsequent response/nonresponse at 8 weeks with a high level of accuracy (72%) and specificity (89%). After 8 weeks, early nonresponders were less likely to achieve symptom remission (P < .001), improved less on functional domains (P < .05), perceived medication as less beneficial (P = .004), and incurred total heath care costs over twice that of early responders ($4349 vs $2102, P = .010). Conclusions: In the usual care of schizophrenia patients, early nonresponse appears to reliably predict subsequent nonresponse to continued treatment with the same medication to be associated with poorer outcomes and higher health care costs. Identifying early nonresponders may minimize prolonging exposure to suboptimal or ineffective treatment strategies.